2015
DOI: 10.1007/s13277-014-3009-3
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-145 is associated with aggressive progression and poor prognosis in human cervical cancer

Abstract: MicroRNAs (miRNAs) play important roles in the processes of tumor initiation and progression. However, miR-145 expression in cervical cancer has been rarely investigated. The aim of this study was to investigate the clinical significance and prognostic value of miR-145 expression in cervical cancer. MiR-145 expression in 114 pairs of human cervical cancer and adjacent normal tissues was detected by real-time quantitative RT-PCR assay. The results showed that miR-145 expression was significantly downregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Also, downregulation of miR‐145‐5p correlated with poor prognosis in gastric cancer . The same conclusion was also obtained in oral squamous cell carcinomas , cervical cancer , osteosarcoma , and prostate cancer .These results convinced us that lower expression of miR‐145 may predict poor prognosis. And a further study is needed to demonstrate this conclusion.…”
Section: Discussionsupporting
confidence: 71%
“…Also, downregulation of miR‐145‐5p correlated with poor prognosis in gastric cancer . The same conclusion was also obtained in oral squamous cell carcinomas , cervical cancer , osteosarcoma , and prostate cancer .These results convinced us that lower expression of miR‐145 may predict poor prognosis. And a further study is needed to demonstrate this conclusion.…”
Section: Discussionsupporting
confidence: 71%
“…These modulated miRNAs in cancer can function as oncogenes or tumor suppressor genes. Studies have reported that miR-145 and miR143 are significantly lower in cervical cancer and expression of these miRNA inhibits growth of cervical cancer cells3435. Our data show a significant (p < 0.01) increase of miR-145 and miR-143 in cervical cancer cells after treatment with Cucurbitacin D, which clearly indicates that Cucurbitacin D may inhibit the growth of cervical cancer cells via inducing the expression of tumor suppressing miR-145 and miR-143.…”
Section: Discussionsupporting
confidence: 61%
“…5Bi) compared to vehicle control. Studies have also demonstrated that expression of miR-145 and miR-143 are significantly lower in cervical cancer when compared with their normal counterparts and over-expression of these miRNAs inhibit growth of cervical cancer cells3435. Thus, we were interested to determine whether Cucurbitacin D treatment restores the expression of these tumor suppressor miRNAs in cervical cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs(miRNAs), a family of 21-25 nucleotide small non-protein-coding RNAs, are significantly involved in a variety of pathophysiological processes such as cell migration, invasion, proliferation and differentiation [12,13]. MicroRNAs can silence target genes efficiently and regulate a broad set of genes of interest simultaneously, which are involved in the initiation, progression and survival of TNBC [14][15][16].…”
Section: Introductionmentioning
confidence: 99%